The effect of the discovery learning strategy on the achievement and retention of second-year intermediate female students in biology. (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of the discovery learning strategy on the achievement and retention of second-year middle school students compared to traditional regular education. The research population consisted of schools affiliated with the First Rusafa Directorate. The school was chosen randomly, and the research sample consisted of two groups. One of them was experimental and its number was 30 students, and the other was a control group and its number was 30 students. The two research groups were qualified according to the variables of the students’ age, calculated in months, intelligence, biology grades for the first semester, and the parents’ academic achievement level. The experimental group was taught according to the discovery learning strategy, while the control group was taught according to the usual method. The experiment was implemented in the second semester. The researcher formulated (100) behavioral objectives and a set of plans that included 18 teaching plans. The test was prepared by the researcher. The test was presented to a group of experts and specialists to verify its validity, apparent validity, and content validity. It was presented to a survey sample to determine the clarity of its paragraphs. The test consisted of 35 multiple choice items, and an agreement rate of 80% was achieved. The difficulty, ease, and discriminatory coefficients were calculated. After applying the test to the sample, the results were as follows: The experimental group outperformed the control group in the achievement test. The effect size was also extracted, and it was 0.90. Also, the experimental group outperformed the control group in the retention test. In this regard, the researcher concluded that a discovery learning strategy should be adopted in teaching biology in the second intermediate stage, due to its important role in raising the level of achievement and retention of biological information among female students. The researcher made a number of recommendations.1- Emphasizing the use of the discovery learning strategy in biology for the second intermediate grade, given its role in raising student achievement and retention.The need to familiarize teachers and instructors with the details and steps of discovery teaching.The need to use the discovery method in teaching biology for the second intermediate grade.Holding in-service training courses for teachers on how to use modern teaching methods, including the discovery learning strategy.Proposals1- A study is being conducted to identify the benefit of the discovery learning strategy in a subject in biology in other variables such as creative thinking, contemplative thinking, and other variables.2-Similar study in other levels of study and other subjects3- A similar study in other regions and for both genders